Aerodynamics of golf balls in still air - Lyu, B.; Kensrud, J.; Smith, L.; Tosaya, T. (Proceedings, 2018)
The following considers lift and drag measurements of 13 production golf ball models propelled through still air in a laboratory setting. The balls travelled at speeds ranging from 18 m/s to 91 m/s and spin ranging from 1500 rpm to 4500 rpm. Speed sensors measured the speed and location of the balls at three locations from which the coefficient of lift and drag were found. The sensors were sufficiently close (3.81 m to 5.08 m) so that the lift and drag effects were nearly constant. Lift and drag were observed to depend on speed, spin rate, and ball model. The difference in the drag coefficient between the ball models were relatively large (>0.1) at low speed (Re < 105), and smaller (<0.05) at high speed (Re > 105). The lift coefficient had a non-linear dependence on spin (fit with a 2nd order polynomial). A trajectory of each ball model was found from the measured lift and drag response. Carry distance varied by 18 m over the models considered here and was not strongly correlated with ball cost.